2017
DOI: 10.1111/cas.13218
|View full text |Cite
|
Sign up to set email alerts
|

Novel small molecule inhibiting CDCP1‐PKCδ pathway reduces tumor metastasis and proliferation

Abstract: CUB domain‐containing protein‐1 (CDCP1) is a trans‐membrane protein predominantly expressed in various cancer cells and involved in tumor progression. CDCP1 is phosphorylated at tyrosine residues in the intracellular domain by Src family kinases and recruits PKCδ to the plasma membrane through tyrosine phosphorylation‐dependent association with the C2 domain of PKCδ, which in turn induces a survival signal in an anchorage‐independent condition. In this study, we used our cell‐free screening system to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…74 Targeting either CDCP1 or PKCd directly may be a better therapeutic strategy because CDCP1 knockout mice are viable with no known pathology. 75 Recently, several strategies for inhibiting CDCP1 and/or PKCd have been developed: i) anti-CDCP1 blocking antibodies prevented tissue colonization and caused poly (ADP-ribose) polymerase 1emediated apoptosis in vivo in a mouse metastasis model 61 ; ii) a small molecule blocking the interaction between CDCP1 and PKCd showed promising antitumor effects in mouse models of gastric cancer and pancreatic cancer 76 ; and iii) a CDCP1 blocking fragment that acts extracellularly inhibited CDCP1 dimerization and PKCd activation and decreased tumor progression and metastasis in two mouse models of TNBC. 44,77 Thus, targeting CDCP1 or PKCd directly to inhibit this protumorigenic arm of SFK signaling may prove to be an effective therapeutic strategy for a subset of TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…74 Targeting either CDCP1 or PKCd directly may be a better therapeutic strategy because CDCP1 knockout mice are viable with no known pathology. 75 Recently, several strategies for inhibiting CDCP1 and/or PKCd have been developed: i) anti-CDCP1 blocking antibodies prevented tissue colonization and caused poly (ADP-ribose) polymerase 1emediated apoptosis in vivo in a mouse metastasis model 61 ; ii) a small molecule blocking the interaction between CDCP1 and PKCd showed promising antitumor effects in mouse models of gastric cancer and pancreatic cancer 76 ; and iii) a CDCP1 blocking fragment that acts extracellularly inhibited CDCP1 dimerization and PKCd activation and decreased tumor progression and metastasis in two mouse models of TNBC. 44,77 Thus, targeting CDCP1 or PKCd directly to inhibit this protumorigenic arm of SFK signaling may prove to be an effective therapeutic strategy for a subset of TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with these results, recent studies reported that loss of CDCP1, in cells kept in nonadherent conditions, supports tumor cells proliferation by differentially regulating SRC activity (23)(24)(25). Interestingly, CDCP1 targeting, either with monoclonal antibodies or small molecule inhibitors, has demonstrated effectiveness at inhibiting tumor growth and metastasis in vivo (26)(27)(28). Since treatments with either SRC or MAPK inhibitors have been associated with poor tolerability in the clinic (29), CDCP1 targeting could represent an excellent and alternative therapeutic option.…”
Section: Cdcp1 Overexpression Drives Prostate Cancer Progression and mentioning
confidence: 95%
“…In addition, previous studies showed that the production of a large number of ROS can activate inflammatory signaling pathways like PI3K/Akt/NF-κB, and promote the expression of type I collagen fibers and TGF-β1, ultimately promoting the occurrence of fibrosis (Cohen-Naftaly and Friedman, 2011;Grochot-Przeczek et al, 2012). Interestingly, SRC can positively promote the production of ROS (Nakashima et al, 2017;Walter et al, 2017), and the rise of ROS induced by different stimuli can further promote the activity of SRC in cells (Kopetz et al, 2009). On the contrary, antioxidants can inhibit the activation of SRC activity by inhibiting ROS production (Fu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%